Coverage compensation algorithm based on vector algebra in hybrid wireless sensor networks - Ning-ning QIN; Li-xia GUO; Bao-guo XU (Tongxin xuebao)
Aiming at the phenomenon that coverage holes caused by energy depletion coexisted with remaining energy of dormant redundant nodes in hybrid wireless sensor networks(WSN),a coverage compensation algorithm based on vector algebra to repair coverage hole with redundant nodes was presented.This algorithm included both the respective dis-placement amount calculation method of all the redundant nodes which may be involved in compensation and policies of the choice of the best redundant nodes that were selected by hole boundary node on the basis of balancing the remaining energy of nodes.The result shows that this algorithm makes full of energy resources in the premise of complete coverage to repair coverage hole,and has a better performance in both movement distance and movement cost compared with ex-isting COA algorithm.